2021
DOI: 10.2147/cmar.s293823
|View full text |Cite|
|
Sign up to set email alerts
|

Circ_HIPK3 Knockdown Inhibits Cell Proliferation, Migration and Invasion of Cholangiocarcinoma Partly via Mediating the miR-148a-3p/ULK1 Pathway

Abstract: Background:The incidence of cholangiocarcinoma (CCA) is on the rise in recent years, and its pathogenesis may be associated with the deregulation of circular RNAs (circRNAs). Hence, we aimed to investigate the role of circRNA homeodomain interacting protein kinase 3 (circ_HIPK3) in CCA. Methods: The expression of circ_HIPK3, miR-148a-3p and unc-51 like kinase 3 (ULK1) mRNA was detected using quantitative real-time polymerase chain reaction (qPCR). The role of circ_HIPK3 in cell proliferation was detected by 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The let-7d-5p and mir-196b-5p miRNAs have proliferation-inducing functions [ 35 , 36 ]. In contrast, the seven downregulated miRNAs (hsa-miR-10a-5p, hsa-miR-10b-5p, hsa-miR-148a-3p, hsa-miR-151a-3p, hsa-miR-196a-5p, hsa-miR-29c-3p, and hsa-miR-654-3p), if expressed, have anti-proliferative, anti-angiogenetic, and pro-inflammatory action [ 37 , 38 , 39 , 40 , 41 , 42 ]. It can be assumed that the downregulation of these miRNAs in HUVEC-sEVs serves to promote proliferation and prevent inflammation in the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…The let-7d-5p and mir-196b-5p miRNAs have proliferation-inducing functions [ 35 , 36 ]. In contrast, the seven downregulated miRNAs (hsa-miR-10a-5p, hsa-miR-10b-5p, hsa-miR-148a-3p, hsa-miR-151a-3p, hsa-miR-196a-5p, hsa-miR-29c-3p, and hsa-miR-654-3p), if expressed, have anti-proliferative, anti-angiogenetic, and pro-inflammatory action [ 37 , 38 , 39 , 40 , 41 , 42 ]. It can be assumed that the downregulation of these miRNAs in HUVEC-sEVs serves to promote proliferation and prevent inflammation in the recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prognostic values of various molecules including gene, miRNAs, and circRNAs were reported to be involved in CCA [ 28 ]. CircRNAs, a novel type of RNA, have a covalent closed-loop structure that plays important roles in many tumors, including CCA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated the pathophysiological roles of circRNAs as ceRNAs in CCA. Other circRNAs identified in recent CCA studies are listed in Table 5 [101][102][103][104][105]. piRNA is a class of small non-coding RNA, which makes an RNA-protein complex with PIWI proteins.…”
Section: Biomarkersmentioning
confidence: 99%